Schwann cells expressing nociceptive channel TRPA1 orchestrate ethanol-evoked neuropathic pain in mice - Francesco De Logu; Simone Li Puma; Lorenzo Landini; Francesca Portelli; Alessandro Innocenti; Daniel Souza Monteiro de Araujo; Malvin N. Janal; Riccardo Patacchini; Nigel W. Bunnett; Pierangelo Geppetti; Romina Nassini (The Journal of Clinical Investigation, 2019)
Excessive alcohol consumption is associated with spontaneous burning pain, hyperalgesia, and allodynia. Although acetaldehyde has been implicated in the painful alcoholic neuropathy, the mechanism by which the ethanol metabolite causes pain symptoms is unknown. Acute ethanol ingestion caused delayed mechanical allodynia in mice. Inhibition of alcohol dehydrogenase (ADH) or deletion of transient receptor potential ankyrin 1 (TRPA1), a sensor for oxidative and carbonyl stress, prevented allodynia. Acetaldehyde generated by ADH in both liver and Schwann cells surrounding nociceptors was required for TRPA1-induced mechanical allodynia. Plp1-Cre Trpa1fl/fl mice with a tamoxifen-inducible specific deletion of TRPA1 in Schwann cells revealed that channel activation by acetaldehyde in these cells initiates a NADPH oxidase-1–dependent (NOX1-dependent) production of hydrogen peroxide (H2O2) and 4-hydroxynonenal (4-HNE), which sustains allodynia by paracrine targeting of nociceptor TRPA1. Chronic ethanol ingestion caused prolonged mechanical allodynia and loss of intraepidermal small nerve fibers in WT mice. While Trpa1–/– or Plp1-Cre Trpa1fl/fl mice did not develop mechanical allodynia, they did not show any protection from the small-fiber neuropathy. Human Schwann cells express ADH/TRPA1/NOX1 and recapitulate the proalgesic functions of mouse Schwann cells. TRPA1 antagonists might attenuate some symptoms of alcohol-related pain.